Similarities and Differences of Hydridic and Protonic Hydrogen Bonding - Lamanec, Maximilián; Zienertová, Jitka; Špeťko, Matej; Nachtigallová, Dana; Hobza, Pavel (Chemphyschem, 2024)
Ab initio calculations were employed to investigate the interactions between selected electron-donating groups, characterized by M-H bonds (where M represents a transition metal and H denotes a hydridic hydrogen), and electron-accepting groups featuring both σ- and π-holes. The study utilized the ωB97X-D3BJ/def2-TZVPPD level of theory. Hydridic hydrogen complexes were found in all complexes with σ- and π-holes. A comparative analysis was conducted on the properties hydridic H-bond complexes, presented here and those studied previously, alongside an extended set of protonic H-bonds complexes. While the stabilization energies changes in M-H bond lengths, vibrational frequencies, intensities of the spectral bands, and charge transfer for these complexes are comparable, the nature of hydridic and protonic H-bonds fundamentally differ. In protonic H-bond complexes, the main stabilization forces arise from electrostatic contributions, while in hydridic H-bond complexes, dispersion energy, is the primary stabilization factor due to the excess of electrons and thus larger polarizability at hydridic H. The finding represents an important characteristic that distinguishes hydridic H-bonding from protonic H-bonds.
Keywords: SAPT; hydrogen bond; charge inverted hydrogen bond; DFT